Pilot tests of augmented realities in science displays and design presentations - Syed Omar, Syed Huzaifah; Jahnkassim, Puteri Shireen; Mahmud, Murni (Teesside University, 2013)
Augmented Reality (AR) enriches the education environment by adding spatially aligned virtual objects (3D models, 2D textures, textual annotations, etc.) by means of special display technologies .This research was a pilot test within a longer research project aimed at investigating and evaluating the relevance of realism elements in 3d AR education technologies in science centers and design presentations. The main advantages of using virtual objects are that they can be animated, they are interactive and can respond to the user’s actions and are not constrained by the costs and practical or physical limitations of real objects. These factors make AR a powerful educational tool. In this research, AR Planets and AR Dinosaur in National Science Center Malaysia were developed as a testbed. A pilot study - to gauge the public reaction to the technology - was developed involving the augmenting of earth globe and a dinosaur. Researchers found out that both adult and children reactions were enthusiastic, changing a dry subject such as science to an exciting activity. A survey was undertaken to gauge the reactions and significance to aspects of realism in AR. User studies were done using field studies to study the effectiveness of realism in AR application in real scenarios. The participants were asked to evaluate two different approaches of application to experience the Augmented 3d science content with heavy realism content and less realism content. After a couple of minutes exploring the content with recorded video, they filled in the questionnaire which assessed their experience towards the application. The importance to the realism elements recorded with the feedback and attitude by the users such as their satisfaction and feel real to the AR content and the feeling of connection to the content elements .The evaluation found out that 98% of the participants believe the AR content with heavy realism elements is superior to compare with AR content with less realism elements in science center. This research will give a better guidance to education centers on user expectations and responses towards such an application including the importance and significance on using realism in Augmented Reality application.